1999
DOI: 10.21273/hortsci.34.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Concentration and Moisture Tension Affect Growth and Foliar N, P, and K Contents of Two Woody Ornamentals

Abstract: Crabapple [Malus ×zumi (Rehd.) `Calocarpa'] and maple (Acer ×freemanii E. Murray `Jeffersred') trees were grown in containers from 22 June to 3 Oct. with three fertilizer concentrations (50, 100, and 200 mg·L-1 N) and two levels of moisture tension in the medium [low setpoint (moist) = 5 kPa and high setpoint (dry) = 18 kPa]. Whole-plant growth was enhanced more by minimizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The paper biocontainer resulted in lower g S and lower net photosynthetic rate than in plastic containers, indicating that the increased water use in biocontainers caused greater water stress and decreased opening of stomata in hydrangea plants. Rose et al (1999) reported plant growth of some woody ornamentals, such as crabapple (Malus ·zumi) and maple (Acer ·freemanii E.), were enhanced more by minimizing water stress than by increasing fertilizer concentration. Biocontainer-produced hydrangea plants were of comparable visual quality as plastic container-produced plants, but had decreased N concentration in the root and in the plant on average.…”
Section: Discussionmentioning
confidence: 99%
“…The paper biocontainer resulted in lower g S and lower net photosynthetic rate than in plastic containers, indicating that the increased water use in biocontainers caused greater water stress and decreased opening of stomata in hydrangea plants. Rose et al (1999) reported plant growth of some woody ornamentals, such as crabapple (Malus ·zumi) and maple (Acer ·freemanii E.), were enhanced more by minimizing water stress than by increasing fertilizer concentration. Biocontainer-produced hydrangea plants were of comparable visual quality as plastic container-produced plants, but had decreased N concentration in the root and in the plant on average.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of water and N management on uptake of other nutrients during production for many crops has not been evaluated fully. With some woody perennial plants, growth is enhanced more by minimizing water stress than by increasing fertility (Rose et al, 1999;Tan and Hogan, 1997).…”
mentioning
confidence: 99%
“…Fertilizer management effects on plant water use and drought stress during production for many crops has not been evaluated fully (Linder et al, 1987;Tan and Hogan, 1997). With some woody perennial plants it is possible that growth can be enhanced more by minimizing water stress than by increasing fertility (Rose et al, 1999).…”
mentioning
confidence: 99%